The impact of communication design on strategy implementation success - a study of commercialised state owned enterprises in the communication technology and courier services sector of Zimbabwe - Mapetere, Denver; Manhiwa, Thelma E.R (IJECM Pub UK, 2021)
The study empirically explored and examined the communication approaches used in communicating strategy execution and to establish their impact on strategy success in Commercialised State Owned Enterprises in Zimbabwe’s Communication Technology and Courier Services Sector. The enquiry was based on a 5 point level of agreement likert scale questionnaire with a total of 478 respondents completed the questionnaire out of a target population of 835 giving a 57% response rate. Survey data was present through descriptive statistics and measures of central tendencies of mean, mode and standard deviation and analysed through ANOVA. Findings of the study indicates that communication approaches used in Commercialised SOE in Zimbabwe such a horizontal, upward, downward and diagonal communication were ineffective in during strategy implementation. Furthermore the communication media; emails, memos, telephone, noticeboards, face to face oral presentations and reports deployed in conveying strategy related matters were generally found to be ineffective. Resultantly strategy execution in Commercialised SOE in Zimbabwe failed to due to delayed reactions to changes, lack of awareness and commitment to strategy implementation efforts influenced by poor communication. The study therefore implores top management teams in Commercialised State Owned Enterprises in Zimbabwe to develop strategy implementation sensitive communication systems increase execution success.